The self-healing mechanism of macro cracks in asphalt mortar and its influencing factors - Grossegger, Daniel (2019)
Road structures deteriorate with advancing time. This is a result of the exposure to aperiodic mechanical stress due to traffic and changes in the chemical composition and physical behaviour due to exposure to atmospheric radicals, radiation and temperature changes. A specific part of the deterioration, namely the occurrence of cracks and involved loss or reduction of mechanical properties, can be partly healed or recovered by the intrinsic ability of asphalt to self-heal. The asphalt component bitumen is responsible for the self-healing occurring at different scale lengths of bituminous materials. This is based on the thermal and viscoelastic properties of bitumen. The self-healing of macro cracks in asphalt mortar is mainly governed by the viscous flow of bitumen rich mortar or mastic from the vicinity of the crack into it. The flow is driven by gravity, capillary force and thermal expansion if a positive temperature change occurs. The asphalt composition, grain structure, filler content, bitumen content, bitumen type, modifications, additives and the temperature change determine the self-healing rate and efficiency, defined as the self-healing ratio. A crucial aspect is the formation of a load bearing connection between the fracture surfaces of a fractured aggregate. This is achieved if bitumen/mastic drains into the crack of the aggregate and adheres the fracture surfaces together. However, this results in a lower breaking resistance. Based on physical principles, a model was developed which regards the self-healing as a flow process between two parallel plates, conceptionally representing a crack. This model was used to accurately fit the self-healing ratios obtained by three-point breaking of asphalt mortar beams. Furthermore, to determine the relation of properties of bitumen on the self-healing of a macro crack, a Pearson correlation analysis was conducted. The bitumen types investigated and used to produce the asphalt mortar beams are commonly used for asphalt production and were similar. The correlation analysis revealed that the self-healing is linearly correlated to the softening point and the surface tension. Other properties were not significantly different, resulting in the similar healing ratios obtained. Pressure, which forces the crack surfaces together and mastic to drain into the crack, was identified to be a main contributor for the self-healing. Pressure can originate from confined thermal expansion, porewater, hydrostatic or mechanical sources. That pressure arising from thermal expansion affected the self-healing was shown as the self-healing rate and the self-healing level increased with increasing temperature difference. The effect of confinement on the thermal expansion was illustrated through two capillary experiments and the crucial influence of the capillary diameter and the flow process. Water filling the crack prevented self-healing. However, during the evaporation of water, the water free crack healed better compared to non-water treated asphalt mortar beams, due to the remaining porewater in the beam. By applying a horizontal/circumferential pressure during the self-healing, higher self-healing ratios were achieved and the self-healing rate was increased, supporting the positive influence of compressive pressure on the crack surface for self-healing. In contrast, uniform pressure did not affect the self-healing.